Znaczenie współpracy lokalnej i regionalnej dla jakości i konkurencyjności produktu ośrodka narciarskiego - Żemła, Michał (Significance of Local and Regional Cooperation for the Quality and Competitiveness of a Skiing Center Product, 2005)
Polish accession to the European Union structures and the change in our home skiers' attitudes may, in the nearest future, result in significant changes regarding the conditions of Polish skiing centers' functioning. The development of a competitive product will require efficient cooperation of all entities, involved in servicing skiers, in a given skiing resort. However, an effective cooperation at a local level becomes just the condition indispensable for further partnership, understood in a broader sense. Polish skiing centers should also cooperate with their closest competitors - neighboring centers, in order to create positive image of the whole region.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 137-142